Pengajian jurisprudens dan falsafah undang-undang – isu-isu yang relevan - Abdul Aziz Bari, (Fakulti Undang - Undang, 2002)

(untitled)
The article seeks to survey the problems of definition, scope and relevance of jurisprudence in law schools in Malaysia. Ranging from the lack of clear definitions, clear direction as well as good literature the problems in the study of jurisprudence have made the lecturers and students less interested in the subject. However given that the law needs to change and adjust to the ever-changing circumstances there is a need to address those issues as jurisprudence is one of the avenues that provides the foundations for such a change. But these are not the only issues of concern as in Malaysia – unlike in the West – religion, particularly Islam, is still relevant and this needs to be taken into account in the study of jurisprudence as well. The teaching and understanding of the syariah may be enhanced in the process